Did Twitter deliberately mislead Elon Musk in his acquisition bid? - HUMPHERY-JENNER, Mark (Institutional Knowledge at Singapore Management University, 2022)
Elon Musk has officially ended his bid to acquire Twitter on the grounds that it misled the market in its disclosures, writes UNSW Business School's Mark Humphery-Jenner